(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
This study talks about financial and administrative corruption in the Mamluk state during the reign of Sultan Al-Nasir Muhammad bin Qalawun and focuses on the role of Christian officials in state institutions in financial and administrative corruption by following up on what was done by Minister Abdul Wahhab bin Sharaf Al-Din Al-Nashw, who had an important role in raising money For the account of Sultan Al-Nasir by legitimate and illegitimate ways with the knowledge and approval of Al-Nasir, and his policy resulted in great opposition to him and his policy, which hastened his elimination